Adoption of improved wheat varieties in eastern and western Terai of Nepal - Subedi, Sanjiv; Ghimire, Yuga N.; Adhikari, Surya P.; Devkota, Deepa; Poudel, Hema K.; Sapkota, Bidya Kiran (Journal of Agriculture and Natural Resources, 2019)
The research was conducted from March to May 2019 for assessment on adoption of improved wheat varieties in two major wheat growing districts of Nepal, Sunsari, and Kailali; one representing eastern and another western Terai. A pre-tested interview schedule was used to collect the primary information; in addition, two Key Informant Surveys were performed. Furthermore, relevant literatures were reviewed for secondary information. The simple random method of sampling was used within the selected areas that were identified in consultation with Agriculture Knowledge Centre and agricultural officials of the local government. Altogether, 194 samples were taken for the purpose of the study, omitting the outliers and incomplete responses. Descriptive statistics, probit regression, and indexing were used for data analysis. Probit econometric model revealed that membership dummy (1% level), age (1% level) number of family members involved in agriculture (1% level), subsidy dummy (5% level), number of schooling years (5%) and loan dummy (10% level) significantly determined the adoption of improved wheat varieties developed after NARC establishment. Furthermore, indexing identified- lack of availability of quality improved seeds (I= 0.80) as the major problem associated with the wheat production followed by poor availability of fertilizers (0.77), labour shortage (0.57), lack of proper irrigation (0.46) and lack of agricultural machines (0.39). The government agricultural institutions should assure access to quality seeds and fertilizers to the farmers; in addition, subsidy on irrigation and agricultural machines allied with agricultural loan to the educated youths could be the point of attraction for wheat cultivation which leads to increased wheat productivity.